Physical Activity Is Associated With Reduced Left Ventricular Mass in Obese and Hypertensive African Americans. (20th March 2017) - Kamimura, Daisuke; Loprinzi, Paul D.; Wang, Wanmei; Suzuki, Takeki; Butler, Kenneth R.; Mosley, Thomas H.; Hall, Michael E.
Abstract: BACKGROUND: Physical activity (PA) has been associated with decreased left ventricular (LV) hypertrophy in previous studies. However, little is known about the relationship between PA and LV structure and factors which influence this relationship among African Americans. METHODS: We evaluated 1, 300 African Americans with preserved LV ejection fraction (EF > 50%) from the Genetic Epidemiology Network of Arteriopathy (GENOA) Study (mean age 62.4 years, 73% women). PA index was calculated as 3 * heavy activity hours + 2 * moderate activity hours + slight activity hours/day. The relationship between PA index and LV structure was evaluated using generalized estimating equation. The association between PA index and LV mass index by age group, sex, body mass index (BMI), history of hypertension, diabetes or coronary heart disease, estimated glomerular filtration rate, and current smoking status were plotted. RESULTS: After adjustment for these factors, higher PA index was independently associated with lower LV mass index ( P < 0.05). There were significant interactions between PA index and obesity (BMI ≥ 30) and history of hypertension on LV mass index ( P for interaction <0.05, for both). Higher PA index was associated with lower LV mass index more in obese or hypertensive participants compared with nonobese or nonhypertensive participants. CONCLUSIONS: Higher PA index was associated with reduced LV hypertrophy in obese and hypertensive African Americans. Prospective studies aimed at assessing whether increasing PA prevents LV hypertrophy and potentially reduces the risk of heart failure in these at risk groups are warranted.